Lepong: A New Obsidian Source in the Admiralty Islands, Papua New Guinea. Issue 3 (10th April 2014) - Summerhayes, Glenn R.; Kennedy, Jean; Matisoo‐Smith, Elizabeth; Mandui, Herman; Ambrose, Wal; Allen, Charlotte; Reepmeyer, Christian; Torrence, Robin; Wadra, François; Buvit, Ian; Carson, Mike T.
<x xml:space="preserve">Abstract</x> A new obsidian source from northwest Manus, Papua New Guinea, is reported for the first time. The chemical signature for this new source was obtained using the electron microprobe, ICP‐MS, and PIXE‐PIGME, and the results were compared with known sources and artifacts from this region. The results show for the first time a more complex scenario of obsidian procurement and exchange than previously thought. Archaeological excavation and survey of Manus is so far very limited, with only one excavated Pleistocene site. Much more archaeological work is needed to find more early sites, to assess the distributions of material from Lepong and other obsidian sources, and model obsidian transfers in more detail.